Treatment of acromegaly patients at the Federal University of Triângulo Mineiro (UFTM): Experience Report (Clinics, 2017)
OBJECTIVE: To evaluate the effectiveness of the treatment of acromegaly patients at the Federal University of Triangulo Mineiro. METHODS: Cross-sectional and retrospective study of thirty cases treated over a period of two decades. RESULTS: 17 men (56.7%) aged 14-67 years and 13 women aged 14-86 years were analyzed. Twenty-one patients underwent transphenoidal surgery, whichwas associated with somatostatin receptor ligands in 11 patients (39.3%), somatostatin receptor ligands + radiotherapyin 5 patients (17.8%), radiotherapy in 3 patients (10.7%), and radiotherapy + somatostatin receptorligands + cabergoline in 1 patient (3.6%). Additionally, 2 patients underwent radiotherapy and surgeryalone. Six patients received somatostatin receptor ligands before surgery, and 2 were not treated due to refusal and death. Nine patients have died, and 20 are being followed; 13 (65%) have growth hormonelevels o1 ng/mL, and 11 have normal insulin-like growth factor 1 levels. CONCLUSION: The current treatment options enable patients seen in regional reference centers to achieve strict control parameters, which allows them to be treated close to their homes.